Fractal Flow Design: How to Design Bespoke Turbulence and Why - Sakai, Yasuhiko; Vassilicos, Christos; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on turbulent flows generated and/or influenced by multiscale/fractal structures. It consists of six chapters which demonstrate, each one in its own way, how such structures and objects can be used to design bespoke turbulence for particular applications and also how they can be used for fundamental studies of turbulent flows.
Urban heat island and fractal sunshade -- Mixing and diffusion in regular/fractal grid turbulence -- Fractal grid generated turbulence: a bridge to practical combustion applications -- Fractal orifices in pipe -- Fractal/multiscale wake generators -- Stochastic analysis of a fractal grid wake.
Keywords: Fluid mechanics; Engineering Fluid Dynamics